Wesley and the Wesleyans - Kent, John 1923- (Cambridge University Press, 2002)
Wesley and the Wesleyans challenges the cherished myth that at the moment when the Enlightenment and the Industrial Revolution were threatening the soul of eighteenth-century England, an evangelical revival - led by the Wesleys - saved it. It will interest anyone concerned with the history of Methodism and the Church of England, the Evangelical tradition, and eighteenth-century religious thought and experience. The book starts from the assumption that there was no large-scale religious revival during the eighteenth century. Instead, the role of what is called 'primary religion' - the normal human search for ways of drawing supernatural power into the private life of the individual - is analysed in terms of the emergence of the Wesleyan societies from the Church of England. The Wesleys' achievements are reassessed; there is fresh, unsentimental description of the role of women in the movement, and an unexpectedly sympathetic picture emerges of Hanoverian Anglicanism
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Wesley, John / 1703-1791; Wesley, John -- 1703-1791; Geschichte 1700-1800; Geschichte; Methodist Church / England / History; Methodismus; Großbritannien